How the tourism industry can help resolve Mongolia's environmental problems - Lian Jing; Peter Stauvermann; Ronald Ravinesh Kumar (Economies, 2025)
In this paper, we use a theoretical model to show that the development of the tourism industry is very likely to significantly reduce environmental problems in Mongolia. Among other issues, Mongolia suffers from an excessively large livestock population, which causes considerable environmental damage. In particular, the excessive livestock population leads to the desertification of the Mongolian steppe, and the emissions of methane and nitrogen dioxide caused by the livestock contribute significantly to Mongolia's greenhouse gas emissions. Our approach essentially relies on creating jobs in the growing tourism industry for those employed in agriculture, using appropriate economic tools. The consequences of such a change include decreasing environmental damages. Particularly, we analyze three policy measures, environmental taxes, lump-sum contributions of hotels to finance advertising, and a tax on profits, to finance advertising expenditures. To support our theoretical results, we show, using available data that it is very plausible to conclude that the GHG emissions caused by additional tourism are far less than the GHG emissions likely to be saved by our economic policy recommendations. This paper shall help economists and interested policymakers to understand how the development of tourism can reduce environmental damages.
Keywords: 330; tourism industry; Mongolia; greenhouse gas emissions; desertification; tourism economics theory; tourism policy